2017
DOI: 10.1155/2017/9124254
|View full text |Cite
|
Sign up to set email alerts
|

TLS-Based Feature Extraction and 3D Modeling for Arch Structures

Abstract: Terrestrial laser scanning (TLS) technology is one of the most efficient and accurate tools for 3D measurement which can reveal surface-based characteristics of objects with the aid of computer vision and programming. Thus, it plays an increasingly important role in deformation monitoring and analysis. Automatic data extraction and high efficiency and accuracy modeling from scattered point clouds are challenging issues during the TLS data processing. This paper presents a data extraction method considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In the south surface example, numbers of control points are 36 in the height direction and 165 in the length direction. The accuracy characteristic of B-spline surfaces in [6,63,67] is proved which adopts 20 control points in the approximation progress regarding an arch structure with the length of 2 m, which indicated that there is a control point every 0.1 m. The determination regarding the quantity of control points affects the quality of the approximated surface. Detailed explanations regarding the parameter and model selection problem are given in [63].…”
Section: B-spline Approximationmentioning
confidence: 96%
See 2 more Smart Citations
“…In the south surface example, numbers of control points are 36 in the height direction and 165 in the length direction. The accuracy characteristic of B-spline surfaces in [6,63,67] is proved which adopts 20 control points in the approximation progress regarding an arch structure with the length of 2 m, which indicated that there is a control point every 0.1 m. The determination regarding the quantity of control points affects the quality of the approximated surface. Detailed explanations regarding the parameter and model selection problem are given in [63].…”
Section: B-spline Approximationmentioning
confidence: 96%
“…The convention of this special situation is to default this as 0 in the recursion work. For detailed explanations, please refer to [12,67].…”
Section: Feature Acquisition Of the Objectmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22] The TLS combined with robotic systems have great prospects, especially for application in the area of intelligent health monitoring. [23][24][25][26][27][28][29] This article is structured as follows: the first section gives an introduction of the research background and motivation; the second section presents the mathematical methods of robust modeling using B-spline surface; the third section describes the details of data used in this study, including simulated data and tunnel measurement data; the fourth and fifth sections show the analysis results of the simulated and measurement data; lastly, the sixth section draws conclusion of the study.…”
Section: Motivationmentioning
confidence: 99%
“…As terrestrial laser scanners have become more available, their applications have become more widespread. [16][17][18][19][20][21][22][23][24][25][26][27][28] Unfolding and projection of the point cloud A framework of crack extraction and analysis is presented in Figure 1 involving five steps. First, the 3D data of tunnel structures was collected utilizing TLS technology; second, we obtained the point cloud projection and transferred the point cloud data to an image file; third, we carried out image preprocessing; fourth, the automatic crack identification was programmed; and, finally, we analyzed the cracks of the tunnels.…”
Section: Tls Measurement and Data Processingmentioning
confidence: 99%